Iron-based materials for the adsorption and photocatalytic degradation of pharmaceutical drugs: A comprehensive review of the mechanism pathway. (February 2023) - Olusegun, Sunday J.; Souza, Taiane G.F.; Souza, Guilhermina de O.; Osial, Magdalena; Mohallem, Nelcy D.S.; Ciminelli, Virginia S.T.; Krysinski, Pawel
Abstract: Adsorption and photocatalytic degradation techniques for removing various contaminants have received broad consideration and acceptance due to their advantages over conventional wastewater treatment techniques. Iron-based materials are among several groups of adsorbents, and photocatalysts that have proven to be effective in pharmaceuticals-based pollutants removal from wastewater. Pharmaceutical drug removal is accompanied by several mechanisms, so there is a deep need for a better understanding of the complexity and development of wastewater treatment using iron-based materials. Therefore, this review examined the mechanism of adsorption and photocatalysis degradation of pharmaceuticals in aqueous solutions by iron-based materials. The adsorption of pharmaceutical drugs was found to be influenced by changes in the solution pH. The mechanism of removal of these contaminants by iron-based materials through adsorption occurred via electrostatic, π-π, and hydrogen bond interactions among others. In the case of photocatalysis, the first mechanism occurred through the formation the hydroxyl radicals due to highly reactive species (electrons and holes) that partook in the reaction processes, while the second mechanism is related to the formation of hydrogen peroxide, H2 O2, by photogenerated electrons in the conduction band and with the well-known photo dissolution of iron oxide leading to free Fe 2+ and Fe 3+ ions. The overall idea of this review is to provide useful information on the mechanisms of adsorption and photocatalytic degradation of pharmaceutical contaminants using iron-based materials. The review summarizes the current understanding and the advances in the pharmaceutical-bearing effluent treatment using nanostructured adsorbents and photocatalysts, including future developments for a cleaner and safer environment. Graphical abstract: Unlabelled Image Highlights: Review on the mechanism's pathway of pharmaceutical drugs (PD). π-π, H-bonding, hydrophobic and electrostatic interactions are the dominating adsorption mechanisms. The significance of hydroxyl and sulfate radicals in the photocatalytic degradation of PD Experimental and computational methods toward understanding the mechanism pathway Future perspective for the ongoing research